Spleen Stiffness and Splenoportal Venous Flow: Assessment Before and After Transjugular Intrahepatic Portosystemic Shunt Placement. (1st February 2013) - Ran, Hai-Tao; Ye, Xiao-Ping; Zheng, Yuan-Yi; Zhang, Da-Zhi; Wang, Zhi-Gang; Chen, Johnson; Madoff, David; Gao, Jing
Abstract : Objectives: To prospectively assess changes in spleen stiffness and splenoportal venous flow before and after transjugular intrahepatic portosystemic shunt (TIPS) placement. Methods: We prospectively evaluated spleen stiffness measured by the mean shear wave velocity with acoustic radiation force impulse imaging and the splenoportal venous velocity with color Doppler sonography in 12 patients (mean age ± SD, 42.6 ± 11.0 years; range, 29–65 years) who underwent TIPS placement for portal hypertension and gastroesophageal bleeding. The mean shear wave velocity and angle‐corrected splenoportal venous velocity at the main portal and splenic veins were measured 1 day before and 3 to 9 days after TIPS placement (mean interval, 6.0 ± 1.95 days; range, 4–10 days) and were compared with portal vein pressure measured during the procedure. Results: There was a significant difference in portal vein pressure before and after TIPS (25.34 ± 6.21 versus 15.66 ± 6.07 mm Hg; P = .0005). After TIPS, the mean shear wave velocity decreased significantly in all 12 cases (3.50 ± 0.46 versus 3.15 ± 0.39 m/s before and after TIPS; P = .00015). The flow velocity at the main portal vein increased significantly after TIPS (22.21 ± 4.13 versus 47.25 ± 12.37 cm/s; P = .0000051). The splenic vein velocity and spleen index measured 25.57 ± 6.98 cm/s and 55.99 ± 21.27 cm 2, respectively, before TIPS and 35.72 ± 11.10 cm/s and 50.11 ± 21.12 cm 2 after TIPS ( P = .0004 and .003). Conclusions: A significant decrease in the mean shear wave velocity and increase in the splenoportal venous velocity occurred with reduced portal vein pressure after TIPS placement. Hence, both parameters can be used as noninvasive quantitative markers for monitoring TIPS function after placement.